factoriser y² - x² + 2x -1
Answers
Answered by
1
y2, -x2 , 2x, -1
answer
answer
Answered by
0
y²-x²+2x-1
=> y²-(x²-2x+1)
=> y²-[(x)²-2×x×1+(1)²]
=> y²-(x-1)²
![(x - y) {}^{2} = {x}^{2} + y {}^{2} - 2xy (x - y) {}^{2} = {x}^{2} + y {}^{2} - 2xy](https://tex.z-dn.net/?f=%28x+-+y%29+%7B%7D%5E%7B2%7D++%3D++%7Bx%7D%5E%7B2%7D++%2B+y+%7B%7D%5E%7B2%7D++-+2xy)
now , using formula
=> a²-b² = (a+b)(a-b)
we have , => (y+x-1)[y-(x-1)]
=> (y+x-1)(y-x+1)
hope this helps
=> y²-(x²-2x+1)
=> y²-[(x)²-2×x×1+(1)²]
=> y²-(x-1)²
now , using formula
=> a²-b² = (a+b)(a-b)
we have , => (y+x-1)[y-(x-1)]
=> (y+x-1)(y-x+1)
hope this helps
Similar questions
Biology,
9 months ago
Physics,
9 months ago
World Languages,
9 months ago
Math,
1 year ago
Physics,
1 year ago
Social Sciences,
1 year ago